Trimethoprim–sulfonamide use during the first trimester of pregnancy and the risk of congenital anomalies†. Issue 2 (24th November 2015) - Hansen, Craig; Andrade, Susan E.; Freiman, Heather; Dublin, Sascha; Haffenreffer, Katie; Cooper, William O.; Cheetham, T. Craig; Toh, Sengwee; Li, De‐Kun; Raebel, Marsha A.; Kuntz, Jennifer L.; Perrin, Nancy; et al.
Abstract: Background: Sulfonamide antibacterials are widely used in pregnancy, but evidence about their safety is mixed. The objective of this study was to assess the association between first‐trimester sulfonamide exposure and risk of specific congenital malformations. Methods: Mother–infant pairs were selected from a cohort of 1.2 million live‐born deliveries (2001–2008) at 11 US health plans comprising the Medication Exposure in Pregnancy Risk Evaluation Program. Mothers with first‐trimester trimethoprim–sulfonamide (TMP‐SUL) exposures were randomly matched 1:1 to (i) a primary comparison group (mothers exposed to penicillins and/or cephalosporins) and (ii) a secondary comparison group (mothers with no dispensing of an antibacterial, antiprotozoal, or antimalarial medication during the same time period). The outcomes were cardiovascular abnormalities, cleft palate/lip, clubfoot, and urinary tract abnormalities. Results: We first identified 7615 infants in the TMP‐SUL exposure group, of which 7595 (99%) were exposed to a combination of TMP‐SUL and the remaining 1% to sulfonamides alone. After matching (1:1) to the comparator groups and only including those with complete data on covariates, there were 20 064 ( n  = 6688 per group) in the primary analyses. Overall, cardiovascular defects (1.52%) were the most common and cleft lip/palate (0.10%) the least common that were evaluated. Compared with penicillin/cephalosporin exposure, and no antibacterial exposure, TMP‐SUL exposure was not associated with statistically significant elevated risks for cardiovascular, cleft lip/palate, clubfoot, or urinary system defects. Conclusions: First‐trimester TMP‐SUL exposure was not associated with a higher risk of the congenital anomalies studied, compared with exposure to penicillins and/or cephalosporins, or no exposure to antibacterials. Copyright © 2015 John Wiley & Sons, Ltd.